Corrigendum to “Multi-layer model requires accurate information of vertical structure to realize its full potential in simulating gross primary production” [Agricultural and Forest Meteorology 379 (2026) 111036] - Jiangliu Xie; Gaofei Yin; Shangrong Lin; Xiaozhou Xin; Hu Zhang; Xinjie Liu; Qinhuo Liu; Aleixandre Verger; Adrià Descals; Iolanda Filella; Josep Peñuelas (Agricultural and Forest Meteorology, 2026)

A satellite-observed shift in the relative importance of water and temperature constraints on grassland photosynthesis in the Tibetan Plateau - Rui Chen; Yajie Yang; Gaofei Yin; Huiqin Pan; Dujuan Ma; Jiangliu Xie; Guodong Zhang; Meilian Wang; Wei Zhao; Qiaoyun Xie; Aleixandre Verger; Adrià Descals; et al. (Global and Planetary Change, 2026)

High Densities of Large Herbivores Rapidly Disrupt Ecosystem Integrity - Jorge Isla; Emmanuel Serrano; Juan A. Calleja; Carlos Hernández‐Castellano; Rafael Alcalá‐Herrera; Elena Albanell; Carlos Alonso; Elena Baraza; Matthew Brolly; Niall Burnside; Ana Burón‐Ugarte; Miquel Capó; et al. (Global Change Biology, 2026)
Human‐induced high densities of large wild herbivores may pose a threat to natural ecosystems, modifying biodiversity and ecosystem functioning. Although the negative impacts on individual taxa and processes are well documented, a comprehensive understanding of how ecosystem integrity responds to high herbivore densities remains limited. This study addresses this gap through an extensive herbivore‐density manipulation experiment conducted in two Mediterranean woodlands. We established two scenarios of high red deer ( Cervus elaphus ) density, representative of some protected areas (~30 individuals·km 2 ) and intensively managed hunting estates (~90 individuals·km 2 ). We monitored 38 metrics encompassing a broad spectrum of biodiversity and functional responses to synthesize the short‐term impacts of high herbivore densities. We revealed an overall 13% decline in ecosystem integrity after one year of exposure to high herbivore densities, with particularly widespread impacts on functional responses and detrimental effects on biodiversity components. We detected rapid declines in plant diversity and a positive response of epigeic invertebrate orders. Conversely, ants (analyzed separately), birds, and small mammals remained mostly unaffected. Functional responses were consistently impaired, including declines in plant regeneration and physiological performance, simplified pollination networks, degraded soil structure, and increased disease vectors. These findings show that human‐induced high herbivore densities rapidly create conditions that disrupt ecosystem integrity, reveal early signs of ecological degradation, and underscore the urgent need for population regulation.

Incorporating Thermal Adaptation and Acclimation Improves Light‐Use Efficiency Modeling for Estimating Gross Primary Production in Tibetan Plateau Grasslands - Gaofei Yin; Jiangliu Xie; Yu Wang; Rui Chen; Yajie Yang; Dujuan Ma; Wenping Yuan; Qiaoyun Xie; Da Wei; Huai Chen; Xinwei Liu; Aleixandre Verger; et al. (Global Change Biology, 2026)
The optimal temperature for photosynthesis (Topt), the temperature at which photosynthesis peaks, is crucial for estimating gross primary production (GPP). Most models, however, apply biome‐specific Topt, overlooking the spatial and temporal variability driven by the genetic adaptation and interannual thermal acclimation of plants, thus introducing systematic error in GPP estimation. We mapped Topt of Tibetan Plateau (TP) grassland averaged over 1982–2018, using satellite‐derived near‐infrared reflectance of vegetation as a proxy of photosynthesis, and projected future Topt under different scenarios of shared socioeconomic pathways (SSPs) using space‐for‐time substitution. We assessed the effects of Topt adaptation on current GPP estimation and acclimation on projected GPP using a light‐use efficiency model (i.e., EC‐LUE model). The spatial heterogeneity of Topt was pronounced across the TP grassland, with higher values in the northeast and lower values in the southwest, averaging 9.32°C ± 3.15°C. Topt tended to increase from 2040 to 2080 across all SSPs, with the slowest increase under SSP1‐2.6 (0.015°C y −1 ) and the fastest increase under SSP5‐8.5 (0.061°C y −1 ). Incorporating Topt adaptation into the EC‐LUE model improved the accuracy of GPP estimation, with R 2 increasing by 7.19% and RMSE decreasing by 11.40%, compared to the model with a fixed Topt. In contrast, ignoring the adaptation of Topt led to systematically lower GPP values across 77.9% of the TP grassland, resulting in an overall reduction of estimated GPP by 7.07% (0.07 g C m −2 d −1 ). Ignoring the acclimation of Topt led to systematically higher projected GPP on the TP, ranging from 2.87% ± 8.96% (SSP1‐2.6) to 3.83% ± 5.97% (SSP3‐7.0) across different scenarios, covering more than 70% of TP regions. These findings highlight the necessity of incorporating both the adaptation and acclimation of Topt into GPP models to enhance the monitoring of the carbon cycle.

A global fitting and local refinement approach for reliable NDVI reconstruction in persistently cloudy mountain regions - Dujuan Ma; Gaofei Yin; Rui Chen; Jiangliu Xie; Yajie Yang; Xiaodan Wu; Guodong Zhang; Wei Zhao; Baodong Xu; Qiaoyun Xie; Adria Descals; Aleixandre Verger; et al. (Global and Planetary Change, 2026)

Multi-layer model requires accurate information of vertical structure to realize its full potential in simulating gross primary production - Jiangliu Xie; Gaofei Yin; Shangrong Lin; Xiaozhou Xin; Hu Zhang; Xinjie Liu; Qinhuo Liu; Aleixandre Verger; Adrià Descals; Iolanda Filella; Josep Peñuelas (Agricultural and Forest Meteorology, 2026)

Soil-atmosphere terpene exchanges in the tropical forest of French Guiana with nitrogen and phosphorus fertilizer application - Kaijun Yang; Joan Llusià; Zhaobin Mu; Jordi Sardans; Catherine Preece; Iolanda Filella; Romà Ogaya; Albert Gargallo-Garriga; Guille Peguero; Laëtitia M. Bréchet; Clément Stahl; Leandro Van Langenhove; et al. (Plant and Soil, 2025)

Heterogeneous elevation-dependence of grassland greenness and greening on the Tibetan plateau - Jiangliu Xie; Gaofei Yin; Qiaoyun Xie; Wei Zhao; Wenping Yuan; Changting Wang; Aleixandre Verger; Adrià Descals; Iolanda Filella; Josep Peñuelas (Agricultural and Forest Meteorology, 2025)

Effects of long-term nighttime warming on extractable soil element composition in a Mediterranean shrubland - Zhaobin Mu; Dolores Asensio; Jordi Sardans; Romà Ogaya; Joan Llusià; Iolanda Filella; Liehua Tie; Lei Liu; Akash Tariq; Fanjiang Zeng; Josep Peñuelas (Science of The Total Environment, 2024)

A screening analysis of foliar terpene emissions of 36 rainforest tree species in French Guiana and their relationships with seasonality - Joan Llusià; Dolores Asensio; Jordi Sardans; Iolanda Filella; Guille Peguero; Oriol Grau; Romà Ogaya; Ifigenia Urbina; Albert Gargallo-Garriga; Lore T. Verryckt; Leandro Van Langenhove; Laëtitia M. Brechet; et al. (Trees, 2024)

Chronic drought alters extractable concentrations of mineral elements in Mediterranean forest soils - Zhaobin Mu; Dolores Asensio; Jordi Sardans; Romà Ogaya; Joan Llusià; Iolanda Filella; Lei Liu; Xinming Wang; Josep Peñuelas (Science of The Total Environment, 2023)

Foliar elementome and functional traits relationships identify tree species niche in F rench G uiana rainforests - Jordi Sardans; Joan Llusià; Romà Ogaya; Helen Vallicrosa; Iolanda Filella; Albert Gargallo‐Garriga; Guille Peguero; Leandro Van Langenhove; Lore T. Verryckt; Clément Stahl; Elodie A. Courtois; Laëtitia M. Bréchet; et al. (Ecology, 2023)
Biogeochemical niche (BN) hypothesis aims to relate species/genotype elemental composition with its niche based on the fact that different elements are involved differentially in distinct plant functions. We here test the BN hypothesis through the analysis of the 10 foliar elemental concentrations and 20 functional‐morphological of 60 tree species in a French Guiana tropical forest. We observed strong legacy (phylogenic + species) signals in the species‐specific foliar elemental composition (elementome) and, for the first time, provide empirical evidence for a relationship between species‐specific foliar elementome and functional traits. Our study thus supports the BN hypothesis and confirms the general niche segregation process through which the species‐specific use of bio‐elements drives the high levels of α‐diversity in this tropical forest. We show that the simple analysis of foliar elementomes may be used to test for BNs of co‐occurring species in highly diverse ecosystems, such as tropical rainforests. Although cause and effect mechanisms of leaf functional and morphological traits in species‐specific use of bio‐elements require confirmation, we posit the hypothesis that divergences in functional‐morphological niches and species‐specific biogeochemical use are likely to have co‐evolved.

Polar-facing slopes showed stronger greening trend than equatorial-facing slopes in Tibetan plateau grasslands - Gaofei Yin; Xinyu Yan; Dujuan Ma; Jiangliu Xie; Rui Chen; Huiqin Pan; Wei Zhao; Changting Wang; Aleixandre Verger; Adrià Descals; Iolanda Filella; Josep Peñuelas (Agricultural and Forest Meteorology, 2023)

Local interpretation of machine learning models in remote sensing with SHAP: the case of global climate constraints on photosynthesis phenology - Adrià Descals; Aleixandre Verger; Gaofei Yin; Iolanda Filella; Josep Peñuelas (International Journal of Remote Sensing, 2023)

Radiation‐constrained boundaries cause nonuniform responses of the carbon uptake phenology to climatic warming in the Northern Hemisphere - Adrià Descals; Aleixandre Verger; Gaofei Yin; Iolanda Filella; Yongshuo H. Fu; Shilong Piao; Ivan A. Janssens; Josep Peñuelas (Global Change Biology, 2023)
Climatic warming has lengthened the photosynthetically active season in recent decades, thus affecting the functioning and biogeochemistry of ecosystems, the global carbon cycle and climate. Temperature response of carbon uptake phenology varies spatially and temporally, even within species, and daily total intensity of radiation may play a role. We empirically modelled the thresholds of temperature and radiation under which daily carbon uptake is constrained in the temperate and cold regions of the Northern Hemisphere, which include temperate forests, boreal forests, alpine and tundra biomes. The two‐dimensionality of the temperature‐radiation constraint was reduced to one single variable, θ , which represents the angle in a polar coordinate system for the temperature‐radiation observations during the start and end of the growing season. We found that radiation will constrain the trend towards longer growing seasons with future warming but differently during the start and end of season and depending on the biome type and region. We revealed that radiation is a major factor limiting photosynthetic activity that constrains the phenology response to temperature during the end‐of‐season. In contrast, the start of the carbon uptake is overall highly sensitive to temperature but not constrained by radiation at the hemispheric scale. This study thus revealed that while at the end‐of‐season the phenology response to warming is constrained at the hemispheric scale, at the start‐of‐season the advance of spring onset may continue, even if it is at a slower pace.

Amazonian biogenic volatile organic compounds under global change - Ana M. Yáñez‐Serrano; Efstratios Bourtsoukidis; Eliane G. Alves; Maite Bauwens; Trissevgeni Stavrakou; Joan Llusià; Iolanda Filella; Alex Guenther; Jonathan Williams; Paulo Artaxo; Katerina Sindelarova; Jana Doubalova; et al. (Global Change Biology, 2020)
Biogenic volatile organic compounds (BVOCs) play important roles at cellular, foliar, ecosystem and atmospheric levels. The Amazonian rainforest represents one of the major global sources of BVOCs, so its study is essential for understanding BVOC dynamics. It also provides insights into the role of such large and biodiverse forest ecosystem in regional and global atmospheric chemistry and climate. We review the current information on Amazonian BVOCs and identify future research priorities exploring biogenic emissions and drivers, ecological interactions, atmospheric impacts, depositional processes and modifications to BVOC dynamics due to changes in climate and land cover. A feedback loop between Amazonian BVOCs and the trends of climate and land‐use changes in Amazonia is then constructed. Satellite observations and model simulation time series demonstrate the validity of the proposed loop showing a combined effect of climate change and deforestation on BVOC emission in Amazonia. A decreasing trend of isoprene during the wet season, most likely due to forest biomass loss, and an increasing trend of the sesquiterpene to isoprene ratio during the dry season suggest increasing temperature stress‐induced emissions due to climate change.

Foliar elemental composition of E uropean forest tree species associated with evolutionary traits and present environmental and competitive conditions - Jordi Sardans; Ivan A. Janssens; Rocio Alonso; Stavros D. Veresoglou; Mathias C. Rillig; Tanja GM Sanders; Jofre Carnicer; Iolanda Filella; Gerard Farré‐Armengol; Josep Peñuelas (Global Ecology and Biogeography, 2015)
Aim Plant elemental composition and stoichiometry are crucial for plant structure and function. We studied to what extent elemental stoichiometry in plants might be strongly related to environmental drivers and competition from coexisting species. Location Europe. Methods We analysed foliar N , P , K , C a and M g concentrations and their ratios among 50 species of E uropean forest trees sampled in 5284 plots across E urope and their relationships with phylogeny, forest type, current climate and N deposition. Results Phylogeny is strongly related to overall foliar elemental composition in European tree species. Species identity explained 56.7% of the overall foliar elemental composition and stoichiometry. Forest type and current climatic conditions also partially explained the differences in foliar elemental composition among species. In the same genus co‐occurring species had overall higher differences in foliar elemental composition and stoichiometry than the non‐co‐occurring species. Main conclusions The different foliar elemental compositions among species are related to phylogenetic distances, but they are also related to current climatic conditions, forest types, drivers of global change such as atmospheric N deposition, and to differences among co‐occurring species as a probable consequence of niche specialization to reduce direct competition for the same resources. Different species have their own ‘fixed’ foliar elemental compositions but retain some degree of plasticity to the current climatic and competitive conditions. A wider set of elements beyond N and P better represent the biogeochemical niche and are highly sensitive to plant function. Foliar elemental composition can thus be useful for representing important aspects of plant species niches.

Changes in floral bouquets from compound‐specific responses to increasing temperatures - Gerard Farré‐Armengol; Iolanda Filella; Joan Llusià; Ülo Niinemets; Josep Peñuelas (Global Change Biology, 2014)
We addressed the potential effects of changes in ambient temperature on the profiles of volatile emissions from flowers and tested whether warming could induce significant quantitative and qualitative changes in floral emissions, which would potentially interfere with plant–pollinator chemical communication. We measured the temperature responses of floral emissions of various common species of Mediterranean plants using dynamic headspace sampling and used GC ‐ MS to identify and quantify the emitted terpenes. Floral emissions increased with temperature to an optimum and thereafter decreased. The responses to temperature modeled here predicted increases in the rates of floral terpene emission of 0.03–1.4‐fold, depending on the species, in response to an increase of 1 °C in the mean global ambient temperature. Under the warmest projections that predict a maximum increase of 5 °C in the mean temperature of Mediterranean climates in the Northern Hemisphere by the end of the century, our models predicted increases in the rates of floral terpene emissions of 0.34–9.1‐fold, depending on the species. The species with the lowest emission rates had the highest relative increases in floral terpene emissions with temperature increases of 1–5 °C. The response of floral emissions to temperature differed among species and among different compounds within the species. Warming not only increased the rates of total emissions, but also changed the ratios among compounds that constituted the floral scents, i.e. increased the signal for pollinators, but also importantly altered the signal fidelity and probability of identification by pollinators, especially for specialists with a strong reliance on species‐specific floral blends.

Remote sensing of atmospheric biogenic volatile organic compounds (BVOCs) via satellite-based formaldehyde vertical column assessments - Shawn C. Kefauver; Iolanda Filella; Josep Peñuelas (International Journal of Remote Sensing, 2014)

Evidence of current impact of climate change on life: a walk from genes to the biosphere - Josep Peñuelas; Jordi Sardans; Marc Estiarte; Romà Ogaya; Jofre Carnicer; Marta Coll; Adria Barbeta; Albert Rivas‐Ubach; Joan Llusià; Martin Garbulsky; Iolanda Filella; Alistair S. Jump (Global Change Biology, 2013)
We review the evidence of how organisms and populations are currently responding to climate change through phenotypic plasticity, genotypic evolution, changes in distribution and, in some cases, local extinction. Organisms alter their gene expression and metabolism to increase the concentrations of several antistress compounds and to change their physiology, phenology, growth and reproduction in response to climate change. Rapid adaptation and microevolution occur at the population level. Together with these phenotypic and genotypic adaptations, the movement of organisms and the turnover of populations can lead to migration toward habitats with better conditions unless hindered by barriers. Both migration and local extinction of populations have occurred. However, many unknowns for all these processes remain. The roles of phenotypic plasticity and genotypic evolution and their possible trade‐offs and links with population structure warrant further research. The application of omic techniques to ecological studies will greatly favor this research. It remains poorly understood how climate change will result in asymmetrical responses of species and how it will interact with other increasing global impacts, such as N eutrophication, changes in environmental N : P ratios and species invasion, among many others. The biogeochemical and biophysical feedbacks on climate of all these changes in vegetation are also poorly understood. We here review the evidence of responses to climate change and discuss the perspectives for increasing our knowledge of the interactions between climate change and life.

Leaf and stand-level carbon uptake of a Mediterranean forest estimated using the satellite-derived reflectance indices EVI and PRI - Martín F. Garbulsky; Josep Peñuelas; Romà Ogaya; Iolanda Filella (International Journal of Remote Sensing, 2013)

Seasonal changes in the daily emission rates of terpenes by Quercus ilex and the atmospheric concentrations of terpenes in the natural park of Montseny, NE Spain - Joan Llusia; Josep Peñuelas; Roger Seco; Iolanda Filella (Journal of Atmospheric Chemistry, 2012)

Methanol as a signal triggering isoprenoid emissions and photosynthetic performance in Quercus ilex - Roger Seco; Iolanda Filella; Joan Llusià; Josep Peñuelas (Acta Physiologiae Plantarum, 2011)

Patterns and controls of the variability of radiation use efficiency and primary productivity across terrestrial ecosystems - Martín F. Garbulsky; Josep Peñuelas; Dario Papale; Jonas Ardö; Michael L. Goulden; Gerard Kiely; Andrew D. Richardson; Eyal Rotenberg; Elmar M. Veenendaal; Iolanda Filella (Global Ecology and Biogeography, 2010)
Aim The controls of gross radiation use efficiency (RUE), the ratio between gross primary productivity (GPP) and the radiation intercepted by terrestrial vegetation, and its spatial and temporal variation are not yet fully understood. Our objectives were to analyse and synthesize the spatial variability of GPP and the spatial and temporal variability of RUE and its climatic controls for a wide range of vegetation types. Location A global range of sites from tundra to rain forest. Methods We analysed a global dataset on photosynthetic uptake and climatic variables from 35 eddy covariance (EC) flux sites spanning between 100 and 2200 mm mean annual rainfall and between −13 and 26°C mean annual temperature. RUE was calculated from the data provided by EC flux sites and remote sensing (MODIS). Results Rainfall and actual evapotranspiration (AET) positively influenced the spatial variation of annual GPP, whereas temperature only influenced the GPP of forests. Annual and maximum RUE were also positively controlled primarily by annual rainfall. The main control parameters of the growth season variation of gross RUE varied for each ecosystem type. Overall, the ratio between actual and potential evapotranspiration and a surrogate for the energy balance explained a greater proportion of the seasonal variation of RUE than the vapour pressure deficit (VPD), AET and precipitation. Temperature was important for determining the intra‐annual variability of the RUE at the coldest energy‐limited sites. Main conclusions Our analysis supports the idea that the annual functioning of vegetation that is adapted to its local environment is more constrained by water availability than by temperature. The spatial variability of annual and maximum RUE can be largely explained by annual precipitation, more than by vegetation type. The intra‐annual variation of RUE was mainly linked to the energy balance and water availability along the climatic gradient. Furthermore, we showed that intra‐annual variation of gross RUE is only weakly influenced by VPD and temperature, contrary to what is frequently assumed. Our results provide a better understanding of the spatial and temporal controls of the RUE and thus could lead to a better estimation of ecosystem carbon fixation and better modelling.

Short-chained oxygenated VOC emissions in Pinus halepensis in response to changes in water availability - Iolanda Filella; Josep Peñuelas; Roger Seco (Acta Physiologiae Plantarum, 2009)

Remote estimation of carbon dioxide uptake by a Mediterranean forest - MARTÍN F. GARBULSKY; JOSEP PEÑUELAS; DARIO PAPALE; IOLANDA FILELLA (Global Change Biology, 2008)
The estimation of the carbon balance in ecosystems, regions, and the biosphere is currently one of the main concerns in the study of the ecology of global change. Current remote sensing methodologies for estimating gross primary productivity are not satisfactory because they rely too heavily on (i) the availability of climatic data, (ii) the definition of land‐use cover, and (iii) the assumptions of the effects of these two factors on the radiation‐use efficiency of vegetation (RUE). A new methodology is urgently needed that will actually assess RUE and overcome the problems associated with the capture of fluctuations in carbon absorption in space and over time. Remote sensing techniques such as the widely used reflectance vegetation indices (e.g. NDVI, EVI) allow green plant biomass and therefore plant photosynthetic capacity to be assessed. However, there are vegetation types, such as the Mediterranean forests, with a very low seasonality of these vegetation indices and a high seasonality of carbon uptake. In these cases it is important to detect how much of this capacity is actually realized, which is a much more challenging goal. The photochemical reflectance index (PRI) derived from freely available satellite information (MODIS sensor) presented for a 5‐year analysis for a Mediterranean forest a positive relationship with the RUE. Thus, we show that it is possible to estimate RUE and GPP in real time and therefore actual carbon uptake of Mediterranean forests at ecosystem level using the PRI. This conceptual and technological advancement would avoid the need to rely on the sometimes unreliable maximum RUE.

On-line screening of soil VOCs exchange responses to moisture, temperature and root presence - Dolores Asensio; Josep Peñuelas; Iolanda Filella; Joan Llusià (Plant and Soil, 2007)

Lonicera Implexa Leaves Bearing Naturally Laid Eggs of the Specialist Herbivore Euphydryas Aurinia have Dramatically Greater Concentrations of Iridoid Glycosides than other Leaves - Josep Peñuelas; Jordi Sardans; Constantí Stefanescu; Teodor Parella; Iolanda Filella (Journal of Chemical Ecology, 2006)

Effects of climatic change on the phenology of butterflies in the northwest Mediterranean Basin - Constantí Stefanescu; Josep Peñuelas; Iolanda Filella (Global Change Biology, 2003)
Phenological changes in response to climatic warming have been detected across a wide range of organisms. Butterflies stand out as one of the most popular groups of indicators of climatic change, given that, firstly, they are poikilothermic and, secondly, have been the subject of thorough monitoring programmes in several countries for a number of decades. Here we provide for the first time strong evidence of phenological change as a consequence of recent climatic warming in butterflies at a Spanish site in the northwest Mediterranean Basin. By means of the widely used Butterfly Monitoring Scheme methodology, three different phenological parameters were analysed for the most common species to test for trends over time and relationships with temperature and precipitation. Between 1988 and 2002, there was a tendency for earlier first appearance dates in all 17 butterfly species tested, and significant advances in mean flight dates in 8 out of 19 species. On the other hand, the shape of the curve of adult emergence did not show any regular pattern. These changes paralleled an increase of 1–1.5°C in mean February, March and June temperatures. Likewise, a correlation analysis indicated the strong negative effect of spring temperature on phenological parameters (i.e. higher temperatures tended to produce phenological advances), and the opposite effect of precipitation in certain months. In addition, there was some evidence to indicate that phenological responses may differ between taxonomic lineages or species with similar diets. We discuss the consequences that these changes may have on species' population abundances, especially given the expected increase in aridity in the Mediterranean Basin caused by current climatic warming. We predict that varying degrees of phenological flexibility may account for differences in species' responses and, for multivoltine species, predict strong selection favouring local seasonal adaptations such as diapause phenomena or migratory behaviour.

Partitioning of water and nitrogen in co-occurring Mediterranean woody shrub species of different evolutionary history - Iolanda Filella; Josep Peuelas (Oecologia, 2003)

Changed plant and animal life cycles from 1952 to 2000 in the Mediterranean region - Josep Peñuelas; Iolanda Filella; PerE. Comas (Global Change Biology, 2002)
The available data on climate over the past century indicate that the earth is warming. Important biological effects, including changes of plant and animal life cycle events, have already been reported. However, evidence of such effects is still scarce and has been mostly limited to northern latitudes. Here we provide the first long‐term (1952–2000) evidence of altered life cycles for some of the most abundant Mediterranean plants and birds, and one butterfly species. Average annual temperatures in the study area (Cardedeu, NE Spain) have increased by 1.4 °C over the observation period while precipitation remained unchanged. A conservative linear treatment of the data shows that leaves unfold on average 16 days earlier, leaves fall on average 13 days later, and plants flower on average 6 days earlier than in 1952. Fruiting occurs on average 9 days earlier than in 1974. Butterflies appear 11 days earlier, but spring migratory birds arrive 15 days later than in 1952. The stronger changes both in temperature and in phenophases timing occurred in the last 25 years. There are no significant relationships among changes in phenophases and the average date for each phenophase and species. There are not either significant differences among species with different Raunkiaer life‐forms or different origin (native, exotic or agricultural). However, there is a wide range of phenological alterations among the different species, which may alter their competitive ability, and thus, their ecology and conservation, and the structure and functioning of ecosystems. Moreover, the lengthening of plant growing season in this and other northern hemisphere regions may contribute to a global increase in biospheric activity.

Herbaria century record of increasing eutrophication in Spanish terrestrial ecosystems - Josep Peñuelas; Iolanda Filella (Global Change Biology, 2001)
Summary Additional biological evidence is presented for the alteration of biogeochemical cycles by human activities. The leaf δ 15 N and the concentrations of nutrients in herbarium specimens of 24 species of vascular plants and 3 species of bryophytes collected in northern and eastern regions of Spain have substantially changed throughout the XX century. In the second half of the century, when anthropogenic nitrogen fixation and mobilization started to increase rapidly, leaf δ 15 N values started to decrease strongly, indicating that additional anthropogenic nitrogen is being retained in Spanish terrestrial ecosystems. The concentration of nutrients in vascular plants did not present any clear pattern, but there were increasing concentrations of N and other nutrients (P, K, and S) in the last decades in bryophytes, which are usually better biomonitors of airborne chemicals than vascular plants. Important consequences for ecosystem structure and functioning such as enhancement of the carbon sink or changes in community biodiversity and species distribution may be expected from this increase in eutrophication.

Leaf mineral concentrations of Erica arborea , Juniperus communis and Myrtus communis growing in the proximity of a natural CO 2 spring - Josep Peñuelas; Iolanda Filella; Roberto Tognetti (Global Change Biology, 2001)
Summary Leaf mineral concentrations of co‐occurring Erica arborea, Juniperus communis and Myrtus communis were measured at bimonthly intervals throughout a year in a natural CO 2 spring and in a nearby control site with similar soil chemistry in a Mediterranean environment. There were different responses to the elevated [CO 2 ] ( c . 700 μL L −1 ) of the spring site plants depending on the element and the species. In the CO 2 spring site K, Ca, Mg, Mn, Al, Fe, and Ti leaf concentrations and the ratio C/N showed significant greater values in at least one or two of the three species. Leaf S concentration were greater in all three species. Leaf concentrations of N, Sr, Co, and B were lower in at least one or two species, and those of C and Ba were lower in all the three studied species near the CO 2 spring. P, Na, Zn, Si, Cu, Ni, Cr, Pb, Mo, V and Cd leaf concentrations and the specific leaf area (SLA, measured in Myrtus communis ) did not show any consistent or significant pattern in response to the elevated [CO 2 ] of the spring site. There was a slight trend towards maximum concentrations of most of these elements during autumn–winter and minimum values during the spring season, especially in Myrtus communis . Multivariate principal component analyses based on the leaf elemental concentrations clearly differentiated the two sites and the three species. Lower concentrations at the spring site were not the result of a dilution effect by increased structural or nonstructural carbon. In contrast to most experimental studies of CO 2 enrichment, mainly conducted for short periods, several of these elements had greater concentrations in the CO 2 spring site. Nutrient acclimation and possible causes including decreased nutrient export, increased nutrient uptake capacity, photosynthetic down‐regulation, Mediterranean water stress, and higher H 2 S concentration in the spring site are discussed.

Altitudinal differences in UV absorbance, UV reflectance and related morphological traits of Quercus ilex and Rhododendron ferrugineum in the Mediterranean region - Iolanda Filella; Josep Peñuelas (Plant Ecology, 1999)

Dependence of Ozone Biomonitoring on Meteorological Conditions of Different Sites in Catalonia (N.E. Spain) - Josep Peñuelas; Angela Ribas; B.S. Gimeno; Iolanda Filella (Environmental Monitoring and Assessment, 1999)